PERMAINAN TRADISIONAL “ENGKLING” UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA, INTERAKSI SOSIAL, DAN SARANA PENDIDIKAN ANTI KORUPSI PADA SISWA SEKOLAH DASAR DI KOTA MADIUN - Eni Winarsih (Universitas PGRI Madiun, 2013)
Classical and conventional teaching and learning indonesian language tends to make the students’ interest decrease and they seem do not care it. It happens because indonesian language has became the second mother tongue after their dialect. Technology in any kinds of games that they are play everyday make them to be individualized children and can not make social interaction with other people well. In fact, there are few children who rarely play traditional games. It happens because they think that traditional game is old-fashioned and not interesting. The aims of this research are to implement and know the effect of “Engkling” games to increase the language skill, social interaction, and media for anti-corruption education for elementary students in Madiun Regency. This research is action research which examine the idea in the form of media and learning strategy using traditional game “Engkling”. The subject of this research are students of MIN Manisrejo Madiun. The collecting data is done by doing some test, observation, and interview. Technique of data validity which is used in this research is data triangulation (source), method triangulation, and informant review. Data analysis using descriptif comparative and critical analysis technique.Traditional game “engkling” is efective to increase the students’ language skill, social interaction, and media for anti-corruption education for elementary students in Madiun Regency. It can be seen from the increasing of teaching and learning qualities. It involves the increasing of their: (1) discipline; (2) interest; (3) activity; (4) the students’ are more active in joining the learning process; (5) responsibility. The values of the anti-curruption education which is taught are thrutful, discipline, and brave. Moreover, the increasing of language skill can be seen from the students’ writing mark that is 81,65 and speaking mark that is 82,65. The KKM is 80, so it can be said that both mark are more than KKM. The mark for students’ social interaction is from the observation through group activities and the result of their mark is 83,25.Keywords: Engkling game, language skill, social interaction, anti-corruption education